Multi-acid-based complex based on heterocyclic fused aromatic ligand, preparation method of multi-acid-based complex and application of multi-acid-based complex to electro-catalysis of nitrate to synthesize ammonia

By preparing polyacid complexes based on heterocyclic fused aromatic ligands, the problems of poor conductivity and easy structural loss of polyacid catalysts in neutral media were solved, achieving efficient nitrate reduction to ammonia synthesis and improving catalytic activity and selectivity.

CN121248604APending Publication Date: 2026-01-02HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511585804.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Existing polyacid catalysts suffer from insufficient conductivity, easy loss of structure, and low catalytic activity and selectivity when electrocatalyzing the reduction of nitrate to ammonia in neutral media.

Method used

A one-step hydrothermal method was used to prepare polyacid complexes based on heterocyclic fused aromatic ligands. 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline was assembled with phosphotungstic acid and nickel ions to form a stable three-dimensional network structure, which enhanced conductivity and structural stability, and improved catalytic activity and selectivity.

Benefits of technology

Highly efficient nitrate reduction for ammonia synthesis was achieved in a neutral medium, with an ammonia yield of up to 7.66 mg·h–1·mg–1cat. and a Faraday efficiency of 75.05%, significantly improving the catalyst's activity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic materials and energy conversion, relates to a polyacid-based complex based on a heterocyclic fused aromatic ligand, a preparation method of the polyacid-based complex and application of the polyacid-based complex to electrocatalytic reduction of nitrate to synthesize ammonia, and aims to solve the problem that an existing polyacid catalyst is insufficient in ammonia production rate in neutral electrolyte. The invention provides a crystal with a chemical formula of [(HNCP) Ni (H2O) 4] 3 [PW12O40] (HNCP is 2-(4-(4-carboxyl phenyl) phenyl) imidazo (4, 5-f) (1, 10) phenanthroline) through a heterocyclic fused aromatic ligand-metal ion-polyacid collaborative design. The preparation method comprises the following steps: dispersing phosphotungstic acid, nickel chloride and HNCP in an ethanol-distilled water mixed solvent, adjusting the pH value, and carrying out solvothermal reaction at 150 DEG C to obtain the product. The maximum ammonia production rate of the complex in a neutral electrolyte at normal temperature and normal pressure can reach 7.66 mg.h <-1 >. Mg-1. Cat., and the complex has important application value in the fields of energy storage and conversion and nitrate pollution abatement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a polyacid complex based on heterocyclic fused aromatic ligands, its preparation method, and its application in electrocatalytic nitrate synthesis of ammonia. The polyacid complex has a well-defined crystal structure and can efficiently achieve electrocatalytic nitrate reduction reaction (NO3RR) to synthesize ammonia in neutral media, providing a reliable technical solution for developing new green and low-energy-consumption ammonia synthesis materials. Background Technology

[0002] Ammonia (NH3), a core raw material for agricultural fertilizers, industrial refrigerants, and rocket propellants, is an indispensable basic chemical in modern industrial systems. However, the current mainstream Haber-Bosch ammonia synthesis process requires high temperature and high pressure (300-500℃, 10-30MPa), which not only consumes enormous amounts of energy but also generates large amounts of CO2 emissions. Therefore, developing a green and sustainable ammonia synthesis technology under ambient temperature and pressure has become a critical technical challenge that urgently needs to be solved.

[0003] Among numerous emerging ammonia synthesis technologies, electrocatalytic nitrate reduction ammonia synthesis (NO3RR) exhibits broad application prospects due to its advantages such as mild reaction conditions (room temperature and pressure), wide availability of raw materials (nitrates can be derived from industrial wastewater or natural water bodies), and environmental friendliness. The core of this technology lies in developing catalysts that possess both high catalytic activity and high selectivity.

[0004] Polyoxometalates (POMs), or simply polyoxometalates, are a class of nano-metal oxometalate clusters with well-defined structures and tunable compositions, characterized by compositional diversity, redox reversibility, and high thermal stability. Among them, [PW 12 O 40 ] 3- abbreviated as {PW 12 Polyacids possess high negative charge numbers, low steric hindrance, and abundant surface-coordinated oxygen atoms. However, most polyacids suffer from high water solubility (easily lost in aqueous solutions) and poor electrical conductivity (affecting electron transfer efficiency), which inhibits their application in the field of electrocatalytic nitrate reduction.

[0005] Polyacid-based organometallic complexes link polyacid clusters or metal ions with organic ligands through coordination bonds, forming hybrid materials that combine the redox properties of polyacids with the structural stability of complexes. This provides an effective approach to solving the aforementioned problems: on the one hand, the chemical bonding between metal ions and organic ligands can construct continuous electron transport pathways, improving the conductivity of the material; on the other hand, the spatial cross-linking of organic ligands can form a three-dimensional network structure, inhibiting the dissolution and loss of polyacids. Furthermore, polyacids, such as {PW... 12 It can act as an electron pool, rapidly transferring electrons to the metal catalytic center and promoting the activation of catalytic active sites.

[0006] Heterocyclic fused aromatic ligands, with their unique structural advantages, have become an ideal choice for solving the aforementioned bottlenecks: First, the fused aromatic ring skeleton of these ligands forms a large π-conjugated system, which can significantly enhance electron delocalization and transport capabilities, effectively compensating for the poor conductivity of polyacids themselves; Second, the abundant N, O, and other heteroatom coordination sites on the fused ring can form stable multi-element coordination bonds with metal ions, and combined with non-covalent interactions such as π-π stacking and hydrogen bonding, construct a rigid three-dimensional network structure, significantly reducing the dissolution and loss of polyacids in the electrolyte; Third, the synergistic effect of the large conjugated system and heteroatoms can precisely regulate the electronic structure of metal active sites, enhancing the resistance to nitrates (NO3-). – The adsorption and activation capabilities of the heterocyclic fused aromatic ligands can suppress the hydrogen evolution competition reaction and improve the selectivity and catalytic activity of ammonia synthesis. In addition, the rigid structure of the heterocyclic fused aromatic ligands can also improve the chemical and electrochemical stability of the material and extend the catalyst cycle life.

[0007] Based on this, this invention, for the first time, selects 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline (HNCP) as a heterocyclic fused aromatic ligand. It possesses a fused, highly conjugated structure of both the imidazolium and o-diazaphenanthroline rings, as well as multiple coordination sites on the O atom of the carboxyl group and the N atom of the heterocycle. This allows it to form stable coordination bonds with nickel ions and further enhance the three-dimensional structural stability and electron transport efficiency of the material through π-π stacking. A one-step hydrothermal method is used to fuse HNCP, nickel ions, and {PW... 12 By assembling, a novel polyacid complex crystal based on heterocyclic fused aromatic ligands was successfully prepared. This crystal exhibited excellent NO3RR ammonia synthesis performance in neutral electrolyte, effectively solving the core technical defects of existing polyacid catalysts such as poor conductivity, easy loss, and low selectivity. Summary of the Invention

[0008] To address the three key technical problems of insufficient conductivity, easy loss of structure, and low catalytic activity and selectivity of existing polyacid catalysts in the electrocatalytic reduction of nitrate to ammonia in neutral media, this invention provides a polyacid complex crystal based on heterocyclic fused aromatic ligands with a well-defined structure, controllable preparation process, and significantly improved catalytic performance, as well as its preparation method and application, filling the technical gap in polyacid NO3RR ammonia synthesis catalysts suitable for neutral media.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] A polyacid complex based on heterocyclic fused aromatic ligands, its preparation method, and its application in electrocatalytic nitrate-to-ammonia synthesis. The structural formula of the complex is as follows:

[0011] [(HNCP)Ni(H2O)4]3[PW 12 O 40 ];

[0012] HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazanphenanthrene);

[0013] Crystal appearance: Orange cuboid shape;

[0014] Crystal system: Trigonal;

[0015] Space Group:

[0016] Unit cell parameters: α = 90°, β = 90°, γ = 120°, unit cell volume

[0017] Core structure: The basic structural unit contains 3 Ni 2+ Ions, 1 {PW 12} cluster and 3 HNCP ligands; Ni 2+ It adopts a six-coordinate mode, combining with two N atoms in the HNCP ligand and four O atoms in the coordinated water molecules to form a one-dimensional molecular chain; the molecular chains are connected by π-π stacking and electrostatic interactions to construct a stable three-dimensional network stacking structure.

[0018] A method for preparing polyacid complexes based on heterocyclic fused aromatic ligands, the specific steps of which are as follows:

[0019] 1. Preparation of a reaction solution with a pH of 3.0–3.2: Phosphotungstic acid, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline were added to ethanol and distilled water and stirred until homogeneous. The pH of the suspension was then adjusted to 3.0–3.2 to obtain a reaction solution with a pH of 3.0–3.2.

[0020] The molar ratio of phosphotungstic acid to nickel chloride mentioned in step one is 1:3.0 to 4.0;

[0021] The molar ratio of phosphotungstic acid to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthrene described in step one is 1:3.0 to 5.0;

[0022] The molar ratio of phosphotungstic acid in step one to the volume ratio of ethanol and distilled water is 0.06 mmol: 5–6 mL.

[0023] 5-6 mL;

[0024] 2. Transfer the reaction solution prepared in step one to a polytetrafluoroethylene reactor, and react at 150℃ for 5 days. After the reaction solution cools to room temperature, wash it to obtain orange cuboid crystals, which are polyacid complexes based on heterocyclic fused aromatic ligands. The chemical formula of this complex is [(HNCP)Ni(H2O)4]3[PW 12 O 40 ], where HNCP is 2-

[0025] (4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline; crystals appear as orange rectangular parallelepipeds; crystal system is trigonal; space group is [missing information]. Cell parameters are

[0026] α=90°, β=90°, γ=120°,

[0027] III. Preparation of an electrocatalytic nitrate reduction electrode based on a polyacid complex with heterocyclic fused aromatic ligands: 20 mg of the polyacid complex based on heterocyclic fused aromatic ligands and 20 mg of acetylene black were ground evenly. 3 mg of the ground sample was added to 125 μL of isopropanol, 10 μL of Nafion solution, and 365 μL of water. The mixture was sonicated for 2 h to obtain a uniformly dispersed mixture. 10 μL of this mixture was dropped onto pretreated carbon cloth and allowed to stand at room temperature for 10 h to obtain a working electrode modified with the polyacid complex based on heterocyclic fused aromatic ligands.

[0028] Compared with the prior art, the beneficial effects of the present invention are:

[0029] I. This invention is the first to successfully prepare a polyacid-based organometallic complex using a one-step hydrothermal synthesis method with 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline organic ligand, phosphotungstic acid, and nickel chloride. The complex exhibits a well-defined structure and excellent stability. X-ray single-crystal diffraction has verified that the chemical formula, crystal system, space group, and cell parameters of the complex are clear and unambiguous. The three-dimensional network stacked structure effectively solves the problem of easy loss of pure polyacid materials in aqueous solutions, significantly improving the structural stability of the material.

[0030] II. The polyacid complex based on heterocyclic fused aromatic ligands prepared in this embodiment is used as an electrocatalyst for nitrate reduction. In neutral medium, this catalyst achieves an ammonia production of up to 7.66 mg / h at -1.3 V vs. RHE voltage. –1 ·mg –1 cat.The Faraday efficiency reached 75.05% at -1.2V vs. RHE voltage. Compared with existing polyacid-based NO3RR catalysts, the ammonia production activity and selectivity were significantly improved, providing a high-performance catalytic solution for the reduction of nitrate to ammonia in neutral media.

[0031] Third, the one-step hydrothermal synthesis method has mild reaction conditions (150℃, atmospheric pressure), readily available raw materials, and easily controllable process parameters. The product has high crystallinity and good reproducibility, making it suitable for large-scale preparation and possessing good prospects for industrial application. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the basic structural unit of a polyacid complex based on heterocyclic fused aromatic ligands, as shown in the example.

[0033] Figure 2 This is a schematic diagram of the structural connection of a polyacid complex based on heterocyclic fused aromatic ligands, as shown in the example.

[0034] Figure 3 This is a schematic diagram of the three-dimensional stacked structure of a polyacid complex based on heterocyclic fused aromatic ligands, as shown in the example.

[0035] Figure 4 The infrared spectrum of a polyacid complex based on heterocyclic fused aromatic ligands is shown in the example.

[0036] Figure 5 Example: UV-Vis absorption spectra of polyacid complexes based on heterocyclic fused aromatic ligands as working electrodes in 0.1M NaNO3 / 0.1M Na2SO4 electrolyte at different voltages.

[0037] Figure 6 Example: A graph showing the relationship between ammonia production and Faraday efficiency at different voltages (-0.8 to -1.3 V vs. RHE) using a polyacid complex based on heterocyclic fused aromatic ligands as the working electrode. Detailed Implementation

[0038] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0039] Specific Implementation Method 1: This implementation method describes a polyacid complex based on heterocyclic fused aromatic ligands, the molecular formula of which is C0. 60 H 60 N 12 Ni3O 58 PW 12 Its basic structural unit contains three Ni2+ Metal ions, a {PW 12} and three HNCP ligands, Ni 2+ It adopts a six-coordinate mode, which binds to two N atoms in the HNCP ligand and four O atoms in the coordinated water molecules, and further constructs a stable three-dimensional network stacking structure through π-π stacking and electrostatic interactions.

[0040] Specific Implementation Method Two: The preparation method of a polyacid complex based on heterocyclic fused aromatic ligands in this implementation method is completed according to the following steps:

[0041] 1. Preparation of reaction solution with pH value of 3.0-3.2: Phosphotungstic acid, nickel chloride and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline were uniformly dispersed in a mixed solvent of ethanol and distilled water and stirred until homogeneous. The pH value of the system was adjusted to 3.0-3.2 to obtain the reaction solution.

[0042] The molar ratio of phosphotungstic acid to nickel chloride mentioned in step one is 1:3.0 to 4.0;

[0043] The molar ratio of phosphotungstic acid to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthrene described in step one is 1:3.0 to 5.0;

[0044] The amount of phosphotungstic acid mentioned in step one, in volume ratio to ethanol and distilled water, is 0.06 mmol: 5-6 mL: 5-6 mL.

[0045] II. Preparation of polyacid-based complexes based on heterocyclic fused aromatic ligands: The reaction solution prepared in step one was transferred to a polytetrafluoroethylene reactor and reacted at 150℃ for 5 days. After the reaction solution cooled to room temperature, it was washed to obtain orange cuboid crystals, which are crystalline materials of polyacid-based complexes based on heterocyclic fused aromatic ligands. The chemical formula of this complex is [(HNCP)Ni(H2O)4]3[PW 12 O 40 HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline; the crystals appear as orange rectangular cuboids; the crystal system is trigonal; the space group is [missing information]. Cell parameters are α=90°, β=90°, γ=120°,

[0046] III. Preparation of an electrocatalytic nitrate reduction electrode based on a polyacid complex with heterocyclic fused aromatic ligands: 20 mg of the polyacid complex based on heterocyclic fused aromatic ligands and 20 mg of acetylene black were ground evenly. 3 mg of the ground sample was added to 125 μL of isopropanol, 10 μL of Nafion solution, and 365 μL of water. The mixture was sonicated for 2 h to obtain a uniformly dispersed mixture. 10 μL of this mixture was dropped onto pretreated carbon cloth and allowed to stand at room temperature for 10 h to obtain a working electrode modified with the polyacid complex based on heterocyclic fused aromatic ligands, which was used to test the nitrate reduction performance.

[0047] The carbon cloth described in step three requires pretreatment. The specific process is as follows: First, soak the carbon cloth in acetone solution and sonicate for 30 minutes. Then, sonicate it three times sequentially in anhydrous ethanol and deionized water, each time for 30 minutes. Finally, completely immerse the carbon cloth in concentrated nitric acid, place it in a reaction vessel, and react at 120°C for 2 hours. After cooling to room temperature, wash with deionized water until the pH is neutral, at which point the carbon cloth is ready for use. Simultaneously, a three-electrode system was selected for electrochemical testing, using the modified glassy carbon electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode.

[0048] Specific Implementation Method 3: The preparation method of the polyacid complex based on heterocyclic fused aromatic ligands described in step one of Specific Implementation Method 2, wherein the molar ratio of phosphotungstic acid, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthrene is 1:3.0~4.0:3.0~5.0.

[0049] Specific Implementation Method Four: The difference between this implementation method and Specific Implementation Method Two is that the nickel salt mentioned in step one is nickel acetate, nickel nitrate, or nickel sulfate. Everything else is the same as in Specific Implementation Methods One to Three.

[0050] Specific Implementation Method 5: The preparation method of the polyacid complex based on heterocyclic fused aromatic ligands described in step one of Specific Implementation Method 2, wherein the molar amount of phosphotungstic acid and the volume ratio of ethanol and distilled water are 0.06 mmol: 5-6 mL: 5-6 mL.

[0051] Specific Implementation Method Six: The difference between this implementation method and Specific Implementation Method Two is that the pH value of the reaction solution in step one is adjusted to 3.0-3.2 using H3PO4 solution and NaOH solution, both with a molar concentration of 1 mol / L. The other steps are the same as in Specific Implementation Methods One through Five.

[0052] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Method Two is that the reaction temperature in step two is 150℃, and the time is 5 days. The other steps are the same as in Specific Implementation Methods One through Six.

[0053] Specific Implementation Method 8: The mass ratio of the phosphotungstic acid complex, acetylene black, isopropanol, and distilled water prepared in step 3 of Specific Implementation Method 2 is 1.5 mg: 1.5 mg: 0.125 mL: 0.365 mL.

[0054] The beneficial effects of the present invention are verified using the following embodiments:

[0055] Example—A method for preparing polyacid complexes based on heterocyclic fused aromatic ligands, implemented according to the following steps:

[0056] I. Preparation of a reaction solution with a pH of 3.1: 0.06 mmol of nickel chloride, 0.02 mmol of phosphotungstic acid, and 0.06 mmol of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-phenanthroline were uniformly dispersed in a mixture of 5 mL of ethanol and 5 mL of distilled water. Then, the pH of the reaction solution was adjusted to 3.1 using 1 mol / L H3PO4 solution and 1 mol / L NaOH solution to obtain a reaction solution with a pH of 3.1.

[0057] The molar ratio of phosphotungstic acid to nickel chloride mentioned in step one is 1:3;

[0058] The molar ratio of phosphotungstic acid to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthrene in step one is 1:3;

[0059] The amount of phosphotungstic acid mentioned in step one, in volume ratio to ethanol and distilled water, is 0.06 mmol: 5 mL: 5 mL.

[0060] 2. Transfer the prepared reaction solution with a pH of 3.1 to an 80 mL polytetrafluoroethylene reactor and react at 150 °C for 5 days. After the reaction solution is cooled to room temperature, wash it to obtain an orange cuboid, which is a polyacid complex crystal based on heterocyclic fused aromatic ligands.

[0061] (I) Structural determination of the polyacid complex crystal based on heterocyclic fused aromatic ligands prepared in Example 1:

[0062] Conclusion ① X-ray crystallographic parameters: see Table 1.

[0063] Table 1. Crystallographic parameters of materials

[0064]

[0065]

[0066] a R1=∑║F o │─│Fc ║ / ∑│F o │. b wR2={∑[w(F o 2 —F c 2 ) 2 ] / ∑[w(F o 2 ) 2 ]} 1 / 2

[0067] Conclusion ② X-ray crystal structure description: X-ray single-crystal diffraction analysis shows that...

[0068] Polyacid complexes based on heterocyclic fused aromatic ligands are trigonal crystal systems. Space group. Cell parameters are α=90°, β=90°, γ=120°, like Figure 1 As shown, the complex contains three Ni 2+ Metal ions, a {PW 12} and three HNCP ligands, Ni 2+ In a six-coordinate mode, it binds to two N atoms in the HNCP ligand and four O atoms in the coordinated water molecules, respectively, and further constructs a stable three-dimensional network structure through π-π stacking interactions and electrostatic interactions (e.g., Figure 3 (As shown).

[0069] Figure 1 This is a schematic diagram of the basic structural unit of a polyacid complex based on heterocyclic fused aromatic ligands, as shown in the example.

[0070] Figure 2 This is a schematic diagram of the structural connection of a polyacid complex based on heterocyclic fused aromatic ligands, as shown in the example.

[0071] Figure 3 This is a schematic diagram of the three-dimensional stacking of polyacid complexes based on heterocyclic fused aromatic ligands, as an example.

[0072] (II) Regarding the polyacid complex [(HNCP)Ni(H2O)4]3[PW] prepared in Example 1 based on heterocyclic fused aromatic ligands. 12 O 40 Infrared spectroscopy characterization was performed to obtain the infrared spectrum of this phosphotungstic acid-based nickel coordination polymer. Figure 4 As shown, at 1077,973,921 and 793 cm -1 The characteristic peaks are attributed to the stretching vibrations ν(P-Oa), ν(W=Od), ν(W-Ob-W), and ν(W-Oc-W), and there is also a 642 cm⁻¹ peak. -1The ν(MO) vibration; the vibration peak is between 1310 and 1727 cm⁻¹. -1 The ligands within the range are classified as organic, and their additional peak confirms the presence of HNCP, at 3449 cm⁻¹. -1 The peak is attributed to the stretching vibration of water molecules in the compound.

[0073] Figure 4 The infrared spectrum of a polyacid complex based on heterocyclic fused aromatic ligands is shown in the example.

[0074] (III) The polyacid complex [(HNCP)Ni(H2O)4]3[PW] prepared in Example 1 based on heterocyclic fused aromatic ligands 12 O 40 Electrochemical performance tests were conducted. A three-electrode system was used, with a glassy carbon electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode. The electrochemical time-current curves of the complex were tested at different voltages in a 0.1M NaNO3 / 0.1M Na2SO4 electrolyte. After 1 hour of measurement, 10 mL of electrolyte from the anolyte was taken for a colorimetric reaction, and the results were measured using a UV-Vis spectrophotometer. Figure 5 As shown, the polyacid complex based on the heterocyclic fused aromatic ligand exhibits high absorbance at -1.3 V vs. RHE, indicating that this complex possesses good electrocatalytic nitrate reduction properties at -1.3 V vs. RHE. Nitrate reduction tests were performed on this working electrode at voltages of -0.8, -0.9, -1.0, -1.1, -1.2, and -1.3 V vs. RHE, as shown... Figure 6 As shown, the complex exhibits a maximum Faraday efficiency of 75.05% at -1.2V vs. RHE, and a maximum ammonia production of 7.66 mg h⁻¹ at -1.3V vs. RHE. -1 mg -1 cat. .

[0075] Figure 5 Example 1: UV-Vis absorption spectra of a polyacid complex based on heterocyclic fused aromatic ligands as the working electrode in 0.1M NaNO3 / 0.1M Na2SO4 electrolyte at different voltages.

[0076] Figure 6 Example—A polyacid complex based on heterocyclic fused aromatic ligands as the working electrode, ammonia production and Faraday efficiency plotted in 0.1M NaNO3 / 0.1M Na2SO4 electrolyte at voltages of -0.8, -0.9, -1.0, -1.1, -1.2 and -1.3V vs. RHE.

[0077] In summary, the polyacid complex based on heterocyclic fused aromatic ligands prepared in Example 1 was used for the electrocatalytic reduction of nitrate. This complex exhibits high catalytic activity towards nitrate and is a high-performance electrocatalytic material, showing potential application value in the field of ammonia synthesis.

Claims

1. A polyacid complex based on heterocyclic fused aromatic ligands, characterized in that, The chemical formula is [(HNCP)Ni(H2O)4]3[PW 12 O 40 HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline; the crystals are orange cuboids; the crystal system is trigonal; the space group is [missing information]. The cell parameter is a = 28.463(6) α=90°, β=90°, γ=120°, Its basic structural unit contains three Ni 2+ Metal ions, a {PW 12 } and three HNCP ligands, Ni 2+ It adopts a six-coordinate mode, which binds to two N atoms in the HNCP ligand and four O atoms in the coordinated water molecules, and further constructs a stable three-dimensional network stacking structure through π-π stacking and electrostatic interactions.

2. A method for preparing a polyacid complex based on a heterocyclic fused aromatic ligand as described in claim 1, characterized in that, Includes the following steps: I. Preparation of a reaction solution with a pH of 3.0–3.2: Phosphotungstic acid, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diazaphenanthroline were uniformly dispersed in a mixed solvent of ethanol and distilled water and stirred until homogeneous. The pH of the system was adjusted to 3.0–3.2 to obtain the reaction solution. The molar ratio of phosphotungstic acid to nickel salt was 1:3.0–4.0, the molar ratio of phosphotungstic acid to HNCP was 1:3.0–5.0, and the molar ratio of phosphotungstic acid to ethanol and distilled water was 0.06 mmol:5–6 mL:5–6 mL. II. Preparation of polyacid complexes based on heterocyclic fused aromatic ligands: The reaction solution prepared in step I was transferred to a polytetrafluoroethylene reactor and reacted at 150°C for 5 days. After the temperature of the reaction solution was reduced to room temperature, it was washed to obtain orange cuboid crystals.

3. The preparation method according to claim 2, characterized in that, The nickel salt is nickel chloride, which can be replaced by nickel acetate, nickel nitrate or nickel sulfate.

4. The preparation method according to claim 2, characterized in that, The molar ratio of phosphotungstic acid, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diaphenanthrene is 1:3.0–4.0:3.0–5.

0. Simultaneously, the structural formula of the organic ligand 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)o-diaphenanthrene is...

5. The preparation method according to claim 2, characterized in that, In step one, the reagents used to adjust the pH value are 1 mol / L H3PO4 solution and 1 mol / L NaOH solution.

6. The preparation method according to claim 2, characterized in that, In the ethanol-distilled water mixed solvent, the volume ratio of ethanol to distilled water is 1:

1.

7. An electrocatalytic nitrate reduction electrode, characterized in that, The polyacid complex based on heterocyclic fused aromatic ligands as described in claim 1 is prepared by the following steps: 20 mg of the polyacid complex based on heterocyclic fused aromatic ligands and 20 mg of acetylene black are ground evenly, and 3 mg of the ground sample is added to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water. The mixture is sonicated for 2 h to obtain a uniformly dispersed mixture. 10 μL of the mixture is dropped onto the pretreated carbon cloth and allowed to stand at room temperature for 10 h to obtain a working electrode modified with the polyacid complex based on heterocyclic fused aromatic ligands.

8. The application of the polyacid complex based on heterocyclic fused aromatic ligands as described in claim 1 in the electrocatalytic reduction of nitrate to ammonia.